Supplementation with fibroblast growth factor 7 during in vitro maturation of porcine cumulus-oocyte complexes improves oocyte maturation and early embryonic development - Zheng, Haomiao; Choi, Hyerin; Oh, Dongjin; Kim, Mirae; Cai, Lian; Jawad, Ali; Kim, Sohee; Lee, Joohyeong; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2023)
In vitro generation of porcine embryos is an indispensable method in the realms of both agriculture and biomedicine. Nonetheless, the extant procedures encounter substantial obstacles pertaining to both the caliber and efficacy of the produced embryos, necessitating extensive research to in vitro maturation (IVM), the seminal commencement phase. One potentially fruitful approach may lie in refining the media and supplements composition utilized for oocyte maturation. Fibroblast growth factor-7 (FGF7), alternatively termed keratinocyte growth factor, is a theca-derived cytokine integral to folliculogenesis. This study aimed to examine the ramifications of supplementing FGF7 during the IVM phase. To determine the FGF7location and its receptor in porcine ovaries, immunohistochemistry was executed based on follicle size categories (1-2, 3-6, and 7-9 mm). Regardless of follicle size, it was determined that FGF7 was expressed in theca and granulosa cells (GCs), whereas the FGF7receptor was only expressed in the GCs of the larger follicles. During the IVM process, the maturation medium was supplied with various concentrations of FGF7, aiming to mature porcine cumulus-oocyte complexes (COCs). The data indicated a significant augmentation in the nuclear maturation rate only within the group treated with 10 ng/mL of FGF7(p<0.05). Post-IVM, the oocytes diameter exhibited a significant expansion in all groups that received FGF7supplementation(p<0.05). Additionally, all FGF7supplemented groups exhibited a substantial elevation in intracellular glutathione levels, coupled with This is a provisional file, not the final typeset article a noticeable reduction in reactive oxygen species levels(p<0.05). With respect to gene expressions related to apoptosis, FGF7 treatment elicited a downregulation of pro-apoptotic genes and an upregulation of anti-apoptotic genes. The expression of genes associated with antioxidants underwent a significant enhancement(p<0.05). In terms of the FGF7 signaling pathway-associated genes, there was a significant elevation in the mRNA expression of ERK1, ERK2, and KITLG (p<0.05). Remarkably, the group of 10ng/mL of FGF7demonstrated an appreciable uptick in the blastocyst formation rate during embryonic development post-parthenogenetic activation(p<0.05). In conclusion, the FGF7supplementation during IVM substantially augments the quality of matured oocytes and facilitates the subsequent development of parthenogenetically activated embryos. These results offer fresh perspectives on improved maturation and following in vitro evolution of porcine oocytes.